A Screening Method for the Isolation of Bacteria Capable of Degrading Toxic Steroidal Glycoalkaloids Present in Potato - Hennessy, Rosanna C.; Jørgensen, Niels O. G.; Scavenius, Carsten; Enghild, Jan. J.; Greve-Poulsen, Mathias; Sørensen, Ole Bandsholm; Stougaard, Peter (Frontiers in Microbiology, 2018)
Potato juice, a by-product of starch processing, is a potential high-value food ingredient due to its high protein content. However, conversion from feed to human protein requires the removal of the toxic antinutritional glycoalkaloids (GAs) α-chaconine and α-solanine. Detoxification by enzymatic removal could potentially provide an effective but also sustainable and environmentally friendly process for potato-derived food protein production. While degradation of GAs by microorganisms has been documented, there exists limited knowledge on the enzymes involved and in particular how bacteria degrade and metabolize GAs. Here we describe a series of methods for the isolation, screening and selection of GA-degrading bacteria. Bacterial cultures from soils surrounding greened potatoes, including the potato peels, were established and select bacterial isolates were studied. Screening of bacterial crude extracts for the ability to hydrolyze GAs was performed using a combination of thin layer chromatography (TLC), high performance liquid chromatography (HPLC) and liquid chromatography mass spectrometry (LC-MS). Analysis of the 16S rRNA sequences revealed that bacteria within the genus Arthrobacter were among the most efficient GA-degrading strains.